Faire parler le « rien » - Marine Gilis (Glad!, 2021)
This article presents the exploration of written archives and the constitution of an oral archive based on the following thesis topic: The experience of sexual liberation of the activists in the Women's Movement in Brittany and Pays de la Loire (1968-1981). How do we find and use archives for a study on sexuality? What should be done in the absence of these archives? How can we link research with the creation and use of oral archives? The written archives relating to feminist struggles in the 1970s in western France are analyzed here. The oral sources referred to come from a collection constituted within the framework of a thesis and of the audiovisual commission of the association Archives du féminisme.